2021
DOI: 10.1002/wrna.1657
|View full text |Cite
|
Sign up to set email alerts
|

The control of polycomb repressive complexes by long noncoding RNAs

Abstract: The polycomb repressive complexes 1 and 2 (PRCs; PRC1 and PRC2) are conserved histone-modifying enzymes that often function cooperatively to repress gene expression. The PRCs are regulated by long noncoding RNAs (lncRNAs) in complex ways. On the one hand, specific lncRNAs cause the PRCs to engage with chromatin and repress gene expression over genomic regions that can span megabases. On the other hand, the PRCs bind RNA with seemingly little sequence specificity, and at least in the case of PRC2, direct RNA-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 354 publications
(903 reference statements)
2
19
0
Order By: Relevance
“…HOTAIR was the first lncRNA to be identified that worked silenced regions of the cellular genome in trans. At the time of its discovery, PRC2 was thought to initiate Polycomb silencing prior to PRC1 recruitment [150]. This result was similar to the model proposed for Xist-mediated recruitment of PRC2 in cis via binding to a region of Xist (RepA) as well as to the anti-sense transcript via a twohairpin structure to PRC2, and therefore PRC2 was thought to bind to similar stem-loop structures [151].…”
Section: Regulation By Rnasupporting
confidence: 68%
See 1 more Smart Citation
“…HOTAIR was the first lncRNA to be identified that worked silenced regions of the cellular genome in trans. At the time of its discovery, PRC2 was thought to initiate Polycomb silencing prior to PRC1 recruitment [150]. This result was similar to the model proposed for Xist-mediated recruitment of PRC2 in cis via binding to a region of Xist (RepA) as well as to the anti-sense transcript via a twohairpin structure to PRC2, and therefore PRC2 was thought to bind to similar stem-loop structures [151].…”
Section: Regulation By Rnasupporting
confidence: 68%
“…Xist also does not interact directly with chromatin, instead thought to increase the concentration of hnRNPK/vPRC1 in the vicinity of the region to be silenced. This is likely a common mechanism used by lncRNAs, at least in embryonic stem cells, where additional RNAs also involved in imprinting (Airn, Kcnq1ot1 and Meg1) interact with hnRNPK and Polycomb proteins [150]. It should be noted that these lncRNAs also participate in gene silencing in a non-polycomb dependent manner, for example by potential transcriptional interference of anti-sense transcripts (notably Airn and Kcnq1ot1) and recruitment of additional silencing proteins including histone deacetylase and demethylases (reviewed in [150]).…”
Section: Regulation By Rnamentioning
confidence: 99%
“…The presence of m 5 C methylation in the XIST transcript prevents the binding of the PRC2 in vitro. In Xist lncRNA, the presence of pseudouridylation and A–I editing sites has been confirmed, however, their roles are unknown at this stage so far [ 170 , 171 ].…”
Section: The Impact Of Lncrna Epigenetics On Lncrna Functionmentioning
confidence: 99%
“…In addition, MALAT1 lncRNA is subject to post-transcriptional m5C modification; five m 5 C sites been found to regulate chromatin-related roles in other lncRNAs, such as HOTAIR and XIST [ 135 ]. Although the exact role played by pseudouridine and inosine modifications remains to be explained, and the presence of each of the three inosines increases the stability of MALAT1 by 2–3 kcal/mol [ 28 , 170 ].…”
Section: The Impact Of Lncrna Epigenetics On Lncrna Functionmentioning
confidence: 99%
“…Xist also does not interact directly with chromatin; it is instead thought to increase the concentration of hnRNPK/vPRC1 in the vicinity of the region to be silenced. This is likely a common mechanism used by lncRNAs, at least in embryonic stem cells, where additional RNAs also involved in imprinting (Airn, Kcnq1ot1 and Meg1) interact with hnRNPK and Polycomb proteins [149]. It should be noted that these lncRNAs also participate in gene silencing in a non-polycomb-dependent manner, for example, by potential transcriptional interference of anti-sense transcripts (notably Airn and Kcnq1ot1) and recruitment of additional silencing proteins including histone deacetylase and demethylases (reviewed in [149]).…”
Section: Regulation By Rnamentioning
confidence: 99%